ISOLATION AND SCREENING OF ENDOPHYTIC MARINE FUNGI FOR CELLULASE PRODUCTION (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
Cellulolytic fungi are potentially useful in biotechnology. Decomposition of substrates containing cellulose can be applied in bioethanol and enzymes production. Fungi are one group of microorganisms that can decompose cellulase materials.  This study aimed to obtain potential cellulolytic fungi isolated from marine habitat. Screening of the fungi was performed using CBM media with different salinity. Six isolates were tested quantitatively for cellulolytic activity using congo red staining. Cellulolytic index of algicolous and manglicolous fungi were lower than those of EN isolate, Veronea sp. KT19, and sponge associate (SMH). Fungi cultured in freshwater and seawater media possessed higher cellulolytic index in compared to those of cultures in 3% NaCl medium. However, freshwater and seawater media showed no significant effect. Cellulolytic index of EN isolate, Veronaea sp. KT19, and SMH after six days of incubation were 1.357; 1.267, and 1.278, respectively. All six isolates potentially produced cellulase in all medium tested. Keywords: Cellulolytic, cellulose, endophytes, enzyme